Predictors of Three-Month Mortality and Hospital Re-Admissions in Patients with Liver Cirrhosis - Durga Lohana, Rehan Anwar Chaudhry, Aroosa Khan, Tahir Mahmood Butt, Muhammad Azam, Ayesha Masood (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The percentage of re-admissions to the hospital & death rates within three months is used as a quality indicator for hospitalized patients with advanced disease of the liver; however, this area of research has not been thoroughly studied in Pakistan. Material & methods: This longitudinal study was conducted from January 2021 to June 2021 in the Medicine department of Sialkot Medical College, Sialkot. The study included individuals with cirrhosis of liver who were admitted to the Inpatient gastroenterology department. A total of 160 patients were studied, & their frequency, diagnostic, and biological variables, as well as re - admission prestige and results after three months of assessment, were all documented. Multi-variate logistic study was used to inspect the impact of these factors on re-admissions and mortality rates. Results: The occurrence of hydro-thorax, Hepato Renal Syndrome (HRS), & portal vein thrombosis was markedly related to the risk of re-admissions within 3 months. The Child turcotte pugh (CTP) C grade, Maddrey’s discriminant function (DF), and the model for end-stage liver disease (MELD) score all noticeably raises the probabilities of re-admissions. The area under curve (AUC) for MELD and DF were 0.928 and 0.927, correspondingly. Both MELD and DF raise the risk of mortality markedly. Conclusion: The current study found that parameters similar to DF and MELD as well as problems like hydro-thorax, hepatorenal syndrome, and PVT, are the most prognostic signifiers of liver cancer side effect to determine the proportion of re - admissions & death rates within three months of patient liberation.